Cultura de seguridad y su relación con el clima organizacional en un proyecto minero en Cajamarca, Perú - La Madrid Peña, Juan Fernando (2022)
This research aimed to determine the relationship between safety culture and organizational climate in a copper mining project, in the context of COVID-19 in Cajamarca, Perú, in the year 2021; it is of practical and non-experimental, transitional type of causal descriptive study; the correlation of the variables was determined with Spearman's Rho and the acceptance of the hypothesis was established by means of bilateral significance. The sample consisted of 60 workers from a copper mining project in Cajamarca, to whom a Likert-type survey was applied, consisting of 28 items. The results indicate a Spearman Rho of 0.901 and a significance level of p = 0.006. Concluding that there is a positive and significant relationship between the safety culture and the organizational climate in a copper mining project, in the context of COVID-19, in Cajamarca, Perú.